PKM Optimalisasi Perpustakaan Pendidikan Sejarah bagi Mahasiswa dalam Menggiatkan Literasi Sumber Belajar Sejarah - Amirullah Amirullah; Jumadi Sahabuddin; Muh. Rasyid Ridha; La Malihu; Dalilul Falihin (Universitas Negeri Makassar, 2023)
History students are currently the object of activating historical literacy where reading sources in history learning are very efficient with the preparation of various historical library facilities which are quite representative and enable students to be more active in studying history learning, however based on visits to the library currently it is still very minimal. So it is necessary to carry out outreach and optimization to actively engage in historical literacy, one of the implementations of which is optimizing the learning resources available to students and the general public. Based on the results of observations, it is considered important to optimize the History Library for students. The activities carried out are outreach in the form of counseling, library management training, and literacy competitions.